Comparative media role during revolutions. (c2016) - Hilal, Razan (2016)
The role of social media in contemporary Arab revolutions has been controversial. This thesis examines the role that media has played in the Egyptian uprising of 2011 in comparison to that of the Iranian Revolution of 1978. The aim is to depict the differences in media roles with the presence of social media during the Egyptian revolution – especially in facilitating the attainment of political mobilizations. The notion of enhanced solidarity through utilizing social media is put to scrutiny via a comparative examination between the two revolutions in general (the prerequisites and tools used) and scholarly work (contemporary research) in particular. The thesis reveals that despite the significant role played by social media in the Egyptian revolution, it doesn‟t demonstrate significant comparative difference as a catalyzing agency.